2008
DOI: 10.1038/sj.onc.1211038
|View full text |Cite
|
Sign up to set email alerts
|

BHLHB3: a candidate tumor suppressor in lung cancer

Abstract: BHLHB3 is a basic helix-loop-helix (bHLH) domaincontaining protein that acts as a transcriptional repressor. We found that BHLHB3 transcript levels were low in three human lung cancer cell lines and downregulated in human lung adenocarcinomas as compared to normal lung tissue. BHLHB3 gene overexpression inhibited colony formation of A549, NCI-H520 and NCI-H596 lung cancer cells. The reduced colony growth was likely due to inhibition of cell proliferation as suggested by the downregulation of cyclin D1 (CCND1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 12 publications
(17 reference statements)
1
16
0
Order By: Relevance
“…BHLHB3 is a clock gene (19, 20), a transcriptional repressor (18) and importantly a tumor suppressor in lung cancer (21). In D-HEp3 cells BHLHB3 is induced by p38 and was positively linked to genes involved in extracellular matrix biology (e.g., collagen-I α1, MMP2) (Fig1B).…”
Section: Resultsmentioning
confidence: 99%
“…BHLHB3 is a clock gene (19, 20), a transcriptional repressor (18) and importantly a tumor suppressor in lung cancer (21). In D-HEp3 cells BHLHB3 is induced by p38 and was positively linked to genes involved in extracellular matrix biology (e.g., collagen-I α1, MMP2) (Fig1B).…”
Section: Resultsmentioning
confidence: 99%
“…2) were proposed, of which includes SRY-box5 (SOX5). [18][19][20][21][22][23][24][25][26][27][28][29] Based on the argument that chromosome 12p12.1 is a frequently altered chromosomal site in prostate cancer and the fact that SOX5 has recently been shown to play a role in several cancer types, including those of testicular, skin, brain, lymph node and nasopharyngeal [19][20][21][22][23] ; the authors decided that further work for this study would be focused on the SOX5 gene. However, it should be stressed that studies on other candidate genes in other identified frequently altered chromosomal regions are also currently underway in our laboratory.…”
Section: Smal-pcr Dna Fingerprints Of Matched Microdissected Normal mentioning
confidence: 99%
“…Of the genes that were not included in the pathway illustrated in Figure 2B, BHLHB3 is implicated as a tumor suppressor in lung cancer [54], and TCF8 expression has been inversely correlated with E-cadherin expression in several cancers [55]. EFCAB3, PGBD5, and TOX2 remain to be defined in the context of tumorigenesis.…”
Section: Resultsmentioning
confidence: 99%